Effect of extraction methods on the physicochemical properties of fiber from bamboo shoot waste - Kamonlak Wicharaew; Trakul Prommajak; Rawisara Ruenwai (Penerbit Universiti Kebangsaan Malaysia, 2019)
Canned bamboo shoot process generated bamboo shoot waste about 50% of raw material. This waste was a rich source of dietary fiber. This study investigates the effect of extraction methods, including (1) water, (2) citric acid, (3) ethanol, acid and base, and (4) enzymatic solution, on the physicochemical properties of dietary fiber of bamboo shoots base and strips. The results indicated that enzymatic extraction of bamboo shoots base provided the highest total dietary fiber (79.05%), soluble dietary fiber (34.72%), water holding capacity (15.08 g/g) and swelling capacity (7.23 mL/g). Therefore, enzymatic extraction of bamboo shoots waste was able to provide a potential dietary fiber which can be used as an ingredient in functional foods.